EXPLORING THE IMPACT OF ARTIFICIAL INTELLIGENCE ON HUMANROBOT COOPERATION IN THE CONTEXT OF INDUSTRY 4.0 - ASAAD, Hawkar; ASKAR, Shavan; KAKAMIN, Ahmed; FAIQ, Nayla (Applied Computer Science, 2024)
The function of Artificial Intelligence (AI) in Human-Robot Cooperation (HRC) in Industry 4.0 is unequivocally important and cannot be undervalued. It uses Machine Learning (ML) and Deep Learning (DL) to enhance collaboration between humans and robots in smart manufacturing. These algorithms effectively manage and analyze data from sensors, machinery, and other associated entities. As an outcome, they can extract significant insights that can be beneficial in optimizing the manufacturing process overall. Because dumb manufacturing systems hinder coordination, collaboration, and communication among various manufacturing process components. Consequently, efficiency, quality, and productivity all suffer as a whole. Additionally, Artificial Intelligence (AI) makes it possible to implement sophisticated learning processes that enhance human-robot collaboration and effectiveness when it comes to assembly tasks in the manufacturing domain by enabling learning at a level that is comparable to human-human interactions. When Artificial Intelligence (AI) is widely applied in Human-Robot Cooperation (HRC), a new and dynamic environment for human-robot collaboration is created and responsibilities are divided and distributed throughout social and physical spaces. In conclusion, Artificial Intelligence (AI) plays a crucial and indispensable role in facilitating effective and efficient Human-Robot Cooperation (HRC) within the framework of Industry 4.0. The implementation of Artificial Intelligence (AI)-based algorithms, encompassing deep learning, machine learning, and reinforcement learning, is highly consequential as it enhances human-robot collaboration, streamlines production procedures, and boosts overall productivity, quality, and efficiency in the manufacturing industry.